2021
DOI: 10.1186/s13018-021-02691-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional mapping of distal humerus fracture

Abstract: Background Distal humerus fractures (DHFs) constitute one-third of elbow fractures approximately. In this study, we aim to define and analyze the fracture lines and morphological features of DHFs using mapping technique. Methods One hundred and two DHFs were retrospectively reviewed. All the computed tomography (CT) data were used to manually reconstruct and virtually reduce the DHF fragments to fit a standard 3D model. Smooth curves were depicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…These four patients were treated using lateral plate longer than 100% of trans-epicondylar distance(TED). It is consistent with result of Wang at el[ 1 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These four patients were treated using lateral plate longer than 100% of trans-epicondylar distance(TED). It is consistent with result of Wang at el[ 1 ].…”
Section: Discussionsupporting
confidence: 93%
“…Distal humerus fracture in adults is one of the most challenging injuries to treat for orthopedic surgeons. Complex regional anatomy containing neurovascular, articular comminution, and a limited point for secure fixation makes it challenging for surgeons to achieve anatomical reduction and stable fixation [ 1 ]. Some orthopedic surgeons are not familiar with distal humeral fractures because of their relatively low incidence in adults [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in fracture mapping has recently been increasing with applications for various anatomical locations [ 16 , 18 , 19 , 20 , 21 , 22 , 23 ]. The previously presented methods have demonstrated an increasing trend in terms of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Dugarte et al showed that a 3D analysis of scapular fracture morphology was more accurate than the 2D method [ 17 ]. This technique has been adapted and applied to several anatomical locations [ 16 , 18 , 19 , 20 , 21 , 22 , 23 ]. Most studies defined a single fracture line transcribed from the position between two fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Distal humeral fractures (DHFs) comprise approximately 2% of all adult fractures and one-third of all humeral fractures [ 1 ]. The complex anatomy of elbow articulation, including the distal humerus, proximal ulna, and radial head, leads to complex intra-articular fractures in the distal humerus.…”
Section: Introductionmentioning
confidence: 99%